Eradication of unresectable liver metastasis through induction of tumour specific energy depletion - Da Huo (Nature Portfolio, 2019)
Treatment of liver metastasis in cancer patients is associated with severe side effects. Here, the authors develop nucleus and mitochondria targeted nanoparticles, conjugated via a cathepsin B sensitive peptide to selectively target liver metastatic cells.